Potensi Air Liur Sebagai Perantara dalam Pemeriksaan Noninvasive pada Hewan Piaraan (POTENTIAL OF SALIVA AS A MEDIATOR FOR THE NONINVASIVE EXAMINATION OF DOMESTIC ANIMALS) - Depamede, Sulaiman Ngongu; Rosyidi, Anwar; Sriasih, Made; ., Dahlanuddin; Yulianti, Enny; ., Suparman (Jurnal Veteriner, 2015)
Saliva as unique biological components of the oral cavity has potential as a mediator for noninvasivebiological test. For future livestock industry the application of noninvasive test is strongly necessary dueto animal welfare porpuse. Until now the research and development of the using saliva as a mediator forinvasive test is predominant for humans, while for livestock or domestic animals is still limited. Techniquesand methods that are commonly used are related to proteomics analysis. With this method a lot of thingsthat can be brought about proteomics of saliva are beneficial to the development of saliva-based biomarkers.Although this method is expensive, researches on the use of saliva in the field of livestock industries areurgently needed. It is expected that noninvasive biological test methods based on saliva as a mediator canbe performed immediately.
Keywords: saliva, animal welfare, non-invasive, domestic animal, proteomic